Effect of different pre-treatments and vacuum drying method on the drying kinetics of pegaga (Centella asiatica L.) leaves - Yunos, N. M.; Ariffin, S. H.; Yusof, Y. A.; Salleh, F. S.M.; Zakaria, R. (Rynnye Lyan Resources, 2025)
The quality and bioactive characteristics of medicinal herbs which are pegaga leaves, must be maintained during processing to ensure their effectiveness. The purpose of this study was to examine how different pre-treatments and vacuum drying affect the drying kinetics of pegaga (Centella asiatica L.) leaves. The study examined four pre-treatment techniques: vacuum blanching, microwave blanching, steam blanching, and water blanching. The Page, Logarithmic, Newton, and Midilli-Kucuk models are used to simulate drying kinetics. Optimizing the drying process is critical since it directly impacts the shelf-life and quality of the product. This requires an understanding of drying kinetics. Out of all the drying models evaluated, the Midilli-Kucuk model provided the best fit for describing the drying behaviour of pegaga leaves. This model had higher R² values (indicating a stronger fit) and lower chi-squared and RMSE values (indicating less error). Steam-blanched pegaga leaves had more uniformity, less shrinking, and a better appearance. The current work revealed that all pre-treatment enhances the crispiness of the pegaga leaves after vacuum drying. The results indicated that the vacuum-blanched dried pegaga leaves showed the highest value of total phenolic content (TPC) and total flavonoid content (TFC), including antioxidant activity. To enable the use of pegaga leaves in a variety of applications, including medicines, nutraceuticals, and functional foods, this study helps to create effective processing processes for maintaining the medicinal qualities of pegaga leaves.